The distinctive idea of modern education - Cole, Clark Stewart (My University, 1904)
Introduction: In considering the aims of modern education, the ends attained, and the means in vogue of attaining these ends, it is interesting to consider its development, the gradual evolution, not only of the methods of education but also of its objects. And this evolution has been as gradual and as same as our industrial or our commercial evolution. Nor was the beginning any less crude and faulty. Very early we see the foreshadowing of our modern ideas of education, and it is only little by little that they have come to be realized. Only a review of the history of formal education will show how slowly, though surely, the world has come to a realization of human individuality as the highest goal of attainment.
Citation: Cole, Clark Stewart. The distinctive idea of modern education. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Education; History of Education; Modern Education; Types of Education; Theses; Manuscripts (documents)